Egypt land and lives of the pharaohs revealed. (Willoughby, N.S.W. Global Book Pub., 2005)
Explores every facet of Egypt's geography, society, history, and culture to build up an intriguing image of what life was like in the land of the pharaohs. --Publisher.
Introducing ancient Egypt -- Origins: predynastic and early dynasti Egypt -- Pyramids: the old kingdom -- Change and continuity: first intermediate middle kingdom and second intermediate period -- Warriors: the new kingdom --Occupation: third intermediate period to Roman period -- The rediscovery of ancient Egypt.
Includes index.
Keywords: Excavations (Archaeology) -- Egypt; Egypt -- Antiquities; Egypt -- Civilization -- To 332 B.C.